Hypothalamic KISS1 Expression, Gonadotrophin‐Releasing Hormone and Neurotransmitter Innervation Vary with Stress and Sensitivity in Macaques. (May 2014) - Bethea, C. L.; Kim, A.; Reddy, A. P.; Chin, A.; Bethea, S. C.; Cameron, J. L.
<x xml:space="preserve">Abstract</x> The present study examined the effect of short‐term psychosocial and metabolic stress in a monkey model of stress‐induced amenorrhaea on the hypothalamic‐pituitary‐gonadal axis. KISS1 expression was determined by in situ hybridisation in the infundibular arcuate nucleus. Downstream of KISS1, gonadotrophin‐releasing hormone (GnRH) axons in lateral areas rostral to the infundibular recess, serum luteinising hormone (LH) and serum oestradiol were measured by immunohistochemistry and radioimmunoassay. Upstream of KISS1, norepinephrine axons in the rostral arcuate nucleus and serotonin axons in the anterior hypothalamus and periaqueductal grey were measured by immunohistochemistry. Female cynomolgus macaques (Macaca fascicularis) characterised as highly stress resilient (HSR) or stress sensitive (SS) were examined. After characterisation of stress sensitivity, monkeys were either not stressed, or mildly stressed for 5 days before euthanasia in the early follicular phase. Stress consisted of 5 days of 20% food reduction in a novel room with unfamiliar conspecifics. There was a significant increase in KISS1 expression in HSR and SS animals in the presence versus absence of stress (P = 0.005). GnRH axon density increased with stress in HSR and SS animals (P = 0.015), whereas LH showed a gradual but nonsignificant increase with stress. Oestradiol trended higher in HSR animals and there was no effect of stress (P = 0.83). Norepinephrine axon density (marked with dopamine β‐hydroxylase) increased with stress in both HSR and SS groups (P ≤ 0.002), whereas serotonin axon density was higher in HSR compared to SS animals and there was no effect of stress (P = 0.03). The ratio of dopamine β‐hydroxylase/oestradiol correlated with KISS1 (P = 0.052) and GnRH correlated with serum LH (P = 0.039). In conclusion, oestradiol inhibited KISS1 in the absence of stress, although stress increased norepinephrine, which may over‐ride oestradiol inhibition of KISS1 expression. We speculate that neural pathways transduce stress to KISS1 neurones, which changes their sensitivity to oestradiol.